1990
DOI: 10.2307/368678
|View full text |Cite
|
Sign up to set email alerts
|

Booker T. Washington in Perspective: Essays of Louis R. Harlan

Abstract: An important aspect of the author's study is the attention given to changing directions in federal Indian policy. If the BIA adhered to a "forced assimilation" policy for a half century, it changed its path in the early 1930s. The change was the result of the public outcry made by reformers such as John Collier, no stranger in the history of Indian policy. It was also the result of the well-known Meriam Report of 1928 which detailed the ills of the boarding school system, a list that included over crowded cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to the criteria of the UTCI (Universal Thermal Climate Index) [112,113], a potential discomfort condition in June can be indicated for 12% of the hours of the month; in December, there a potential discomfort can be experienced for 88% of the hours of the month. The average NDVI (Normalized Difference Vegetation Index) [114], evaluated on the base of Sentinel2 data, in June 2018 is M:0.25 s.d. :0.00813, and in December 2019 is M: 0.11 s.d.…”
Section: Methodsmentioning
confidence: 99%
“…According to the criteria of the UTCI (Universal Thermal Climate Index) [112,113], a potential discomfort condition in June can be indicated for 12% of the hours of the month; in December, there a potential discomfort can be experienced for 88% of the hours of the month. The average NDVI (Normalized Difference Vegetation Index) [114], evaluated on the base of Sentinel2 data, in June 2018 is M:0.25 s.d. :0.00813, and in December 2019 is M: 0.11 s.d.…”
Section: Methodsmentioning
confidence: 99%
“…there is a prominent increase in research activities exploring UAV technologies, with a specific emphasis on topics such as "olive tree volume" and "image segmentation" using MSP images and the Normalized Difference Vegetation Index (NDVI) [42]. A recent emergence of advanced technologies such as "machine learning" and "deep learning" in the cluster analysis is evident.…”
Section: Introductionmentioning
confidence: 99%
“…These findings emphasise the crucial role of the CWSI in evaluating irrigation management and its consequent impact on crop productivity. In a distinctive approach using different wavelengths, Marino et al [37] investigated the potential of the Photochemical Reflectance Index (PRI) [38], Water Index (WI) [39], and Normalised Difference Vegetation Index (NDVI) [40] to detect plant responses to seasonal drought. The authors concluded that these indices effectively discriminate the effects of drought on rainfed trees and their subsequent recovery.…”
Section: Introductionmentioning
confidence: 99%